PHYSIOLOGICAL STUDIES IN FUSARIUM SOLANI CAUSING RHIZOME ROT OF GINGER (ZINGIBER OFFICINALE ROSC.) - P. K. RAMTEKE; S.S. KAMBLE (The Bioscan, 2011)
The effect of carbon and nitrogen sources, temperature, pH levels and light spectra on mycelial growth of benomyl sensitive and resistant isolates of Fusarium solani (Mart.) Sacc. was investigated. Sucrose was found to be the best source of carbon, whereas calcium nitrate was the best source of nitrogen. The fungus grew at temperatures ranging from 10 to 35ºC, with optimum growth at 25ºC and no growth was observed at 5ºC and 40ºC. The most suitable pH level for the growth was 4.5. The growth was reduced under different light spectra when compared to darkness. Resistant isolate had higher growth rate as compared to sensitive isolate. Fusarium solani Carbon, Nitrogen pH, Light Temperature, Growth